Loop-mediated isothermal amplification-lateral-flow dipstick (LAMP-LFD) to detect Mycoplasma ovipneumoniae - Zhang, Jie (World J Microbiol Biotechnol, 2019)
In order to establish a rapid detection method for Mycoplasma ovipneumoniae, this study used the loop-mediated isothermal amplification (LAMP) technique to carry out nucleic acid amplification and chromatographic visualization via a lateral flow dipstick (LFD) assay. The M. ovipneumoniae elongation factor TU gene (EF-TU) was detected using a set of specific primers designed for the EF-TU gene, and the EF-TU FIP was detected by biotin labeling, which was used in the LAMP amplification reaction. The digoxin-labeled probe specifically hybridized with LAMP products, which were visually detected by LFD. Here, we established the M. ovipneumoniae LAMP-LFD rapid detection method and tested the specificity, sensitivity, and clinical application of this method. Results showed that the optimized LAMP performed at 60 °C for 60 min, and LFD can specifically and visually detect M. ovipneumoniae with a minimum detectable concentration at 1.0 × 10(2) CFU/mL. The sensitivity of LAMP-LFD was 1000 times that of the conventional PCR detection methods, and the clinical lung tissue detection rate was 86% of 50 suspected sheep infected with M. ovipneumoniae. In conclusion, LAMP-LFD was established in this study to detect M. ovipneumoniae, a method that was highly specific, sensitive, and easy to operate, and provides a new method for the prevention and diagnosis of M. ovipneumoniae infection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11274-019-2601-5) contains supplementary material, which is available to authorized users.